Desenvolvimento e avaliação de dispositivo de anestesia odontológica controlado por computador - Lima, Augusto Darwin Moreira de Araújo (2018)
The present work aims at the development and evaluation of a computer controlled dental anesthesia device. Taking into consideration the technical aspects that can lead to pain during anesthesia, four different technologies were developed: control of the anesthetic fluid flow, tissue vibration around the needle puncture, control of the initial puncture of the needle and control of needle penetration velocity. Thus, in 2013, a patent was filed with INPI, presented in chapter 1. A prototype of this equipment was built, then contemplating the technologies developed, and a clinical evaluation was subsequently carried out, which aimed to compare, in relation to the pain, the equipment developed - called the Computer Controlled Anesthesia Device (DACC) - with the syringe carpule, presented in Chapter 2. In this clinical study with control group and random lottery of the groups, 116 patients were anesthetized, 58 children and 58 adults, divided into Control Group (conventional syringe) and Experimental Group (Computer Controlled Anesthesia Device - DACC). The procedures using the carpule syringe were performed by dental surgeons and, with the DACC, by the researcher himself. For the comparison of syringes, the questionnaire of Fear (CFSS) was used, in order to determine the degree of anxiety of the patients; to determine pain and behavior during the procedure, different scales: Frankl Scale (only in children), Facial Anxiety Scale (FAS), Analog Visual Scale (VAS) and Eyes and Movements (SEM) Scale. It was observed, as a result, that in both children and adults, DACC caused less pain and presented a better behavior than the conventional syringe. There was a statistically significant difference for the Frankl, VAS and SEM scales, evaluated by the Wilcoxon-Mann-Whitney test and the Mann Whitney test. With regard to pain during its application, it was verified that the DACC presented advantages over the carpule syringe.